Financial Integration and Economic Synchronisation (Theoretical Analysis) - Kutsarov, Iliya (Research Papers, 2020)
This study examines various mechanisms for the linkage between financial integration and business cycle synchronization. The present study advocates that changes in capital demand lead to divergence while shocks in the integrated financial system cause synchronization. Based on this differentiation the study derives indicators that determine the tendency for synchronization or divergence.